The roots of the equation x 4 − 1 4 x 3 + 5 1 x 2 + a x + b = 0 are found to be in an arithmetic progression . Find the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the roots of this quartic equation be A − 2 3 D , A − 2 D , A + 2 D , A + 2 3 D , where D > 0 .
By Vieta's formula , ( A − 2 3 D ) + ( A − 2 D ) + ( A + 2 D ) + ( A + 2 3 D ) = 1 4 ⟹ A = 2 7 And the 2 nd symmetric sum of these 4 numbers is equal to 51. For simplicities sake, let A 1 , A 2 , A 3 , A 4 be these numbers. A 1 A 2 + A 1 A 3 + A 1 A 4 + A 2 A 3 + A 2 A 4 + A 3 A 4 = 5 1 Grouping them as such: A 1 ( A 2 + A 3 ) + A 4 ( A 2 + A 3 ) + A 1 A 4 + A 2 A 3 = ( A 1 + A 4 ) ( A 2 + A 3 ) + A 1 A 4 + A 2 A 3 Then substitute: 2 A ⋅ 2 A + ( A 2 − 4 9 D 2 ) + ( A 2 − 4 D 2 ) = 5 1 with A = 2 7 , we get D = 3 .
So the 4 roots are − 1 , 2 , 5 , 8 , thus the quartic equation is ( x + 1 ) ( x − 2 ) ( x − 5 ) ( x − 8 ) = x 4 − 1 4 x 3 + 5 1 x 2 − 1 4 x − 8 0 = 0 with ( a , b ) = ( − 1 4 , − 8 0 ) ⟹ a + b = − 9 4 .
Let the four roots be in arithmetic progression: r , r + δ , r + 2 δ , r + 3 δ such that by Vieta's Formulae:
Σ i = 1 4 r i = 4 r + 6 δ = 1 4 ;
Σ i = 1 3 Σ j = i + 1 4 r i r j = 6 r 2 + 1 8 δ r + 1 1 δ 2 = 5 1
which yields ( r , δ ) = ( − 1 , 3 ) ; ( 8 , − 3 ) , and the four roots are − 1 , 2 , 5 , 8 . Now we calculate:
a = − [ Σ i = 1 2 Σ j = i + 1 3 Σ k = j + 1 4 r i r j r k ] = − 1 4 ;
b = Π i = 1 4 r i = − 8 0
Hence, a + b = − 9 4 .
Problem Loading...
Note Loading...
Set Loading...
Let the first term and the common difference of the arithmetic progression be a 1 and d respectively. Then the four roots are a 1 , a 1 + d , a 1 + 2 d , and a 1 + 3 d . By Vieta's formula we have:
a 1 + ( a 1 + d ) + ( a 1 + 2 d ) + ( a 1 + 3 d ) = 4 a 1 + 6 d = 1 4 ⟹ 2 a 1 + 3 d = 7 . . . ( 1 )
a 1 ( a 1 + d ) + a 1 ( a 1 + 2 d ) + a 1 ( a 1 + 3 d ) + ( a 1 + d ) ( a 1 + 2 d ) + ( a 1 + d ) ( a 1 + 3 d ) + ( a 1 + 2 d ) ( a 1 + 3 d ) = 6 a 1 2 + 1 8 a d 1 + 1 1 d 2 = 5 1 . . . ( 2 )
( 1 ) 2 : 4 a 1 2 + 1 2 a 1 d + 9 d 2 ( 2 ) − ( 3 ) : 2 a 1 2 + 6 a 1 d + 2 d 2 ( 4 ) × 2 : 4 a 1 2 + 1 2 a 1 d + 4 d 2 ( 3 ) − ( 5 ) : 5 d 2 ⟹ d ( 1 ) : ⟹ a 1 = 4 9 = 2 = 4 = 4 5 = 3 = 2 7 − 3 ( 3 ) = − 1 . . . ( 3 ) . . . ( 4 ) . . . ( 5 )
Then the four roots are − 1 , 2 , 5 , and 8 . And a and b are:
a b ⟹ a + b = − ( ( − 1 ) ( 2 ) ( 5 ) + ( − 1 ) ( 5 ) ( 8 ) + ( − 1 ) ( 8 ) ( 2 ) + ( 2 ) ( 5 ) ( 8 ) ) = − 1 4 = ( − 1 ) ( 2 ) ( 5 ) ( 8 ) = − 8 0 = − 9 4